Multiplex sequencing for EZH2, CD79B, and MYD88 mutations using archival cytospin preparations from B‐cell non‐Hodgkin lymphoma aspirates previously tested for MYC rearrangement and IGH/BCL2 translocation. Issue 7 (23rd March 2015) - da Cunha Santos, Gilda; Saieg, Mauro Ajaj; Ko, Hyang Mi; Geddie, William R.; Boerner, Scott L.; Craddock, Kenneth J.; Crump, Michael; Bailey, Denis
<x xml:space="preserve">Abstract</x> BACKGROUND Gene rearrangements and specific translocations define some B‐cell non‐Hodgkin lymphoma (NHL) subtypes. Genome‐wide mutational studies have revealed recurrent point mutations with prognostic implications. The goals of this study were to evaluate the feasibility of applying a multiplex mutation assay to archival cytospin preparations (CPs) and to investigate the rate of EZH2, CD79B, and MYD88 mutations in B‐cell NHL samples previously tested for MYC rearrangement and/or IGH/BCL‐2 translocation. METHODS DNA was extracted from archival CPs of B‐cell NHL cases with previous fluorescence in situ hybridization (FISH) assays for MYC rearrangement and/or IGH/BCL‐2 translocation. Multiplex sequencing was performed for the detection of EZH2 (Y641), CD79B (Y196), and MYD88 (L265) mutations. Sanger sequencing was applied to samples with positive results and failed assays. RESULTS Eighty‐eight archival CPs were available from 40 patients. Alterations detected by FISH were: MYC rearrangement (10 cases), IGH/BCL‐2 translocations (21 cases), dual translocations (6 cases), and other abnormalities for IGH/BCL‐2 (23 cases) and for MYC (16 cases). DNA concentration ranged from 1.88 to 62.85 ng/µL (mean, 9.46 ng/µL). Successful results were obtained in 88.0% of the specimens submitted to multiplex sequencing. With Sanger sequencing, 2 additional mutated cases were found, and all cases with mutations were confirmed. Eight specimens showed mutations: 6 for EZH2, 1 for CD79B, and 1 for MYD88. Among them, 5 cases showed concurrent MYC and/or IGH/BCL‐2 translocations and 2 revealed abnormal signals of IGH/BCL‐2 and MYC. CONCLUSIONS CPs archived for up to 6 years are a reliable source of high‐quality genomic material for multiplex sequencing. Almost all B‐cell NHL with point mutations showed concurrent chromosomal abnormalities. Cancer (Cancer Cytopathol) 2015;123:413‐20. © 2015 American Cancer Society.